Psychological Well-being of Cancer Patients - R.N. Mustafin; E.A. Kalyuzhny (Клиническая и специальная психология)
Formulation of the Problem. In Russia, 2.73% of the population suffer from malignant neoplasms regardless of age. An important factor in successful treatment of cancer patients is psychological well-being, including the presence of positive emotions, engagement, meaning in life, autonomy, positive relationships with others, self-acceptance, and absence of psychological disorders. Actuality. According to scientific articles published between 2005 and present on Scopus, WoS, PubMed, cancer patients are characterized by impaired psychological well-being and require psychological support. Over 1/3 of them experience distress, depression, anxiety, demoralization, and suicidal ideation, which significantly reduces their chances of a favorable outcome. Summary. Positive components of psychological well-being are an important condition for recovery, as modern therapy allows over 60% of cancer patients to survive. Despite the need for psychological support, patients with malignant tumors are characterized by low rates of treatment and a high prevalence of psychological disorders. Violation of psychological well-being contributes to patients’ non-compliance with prescribed treatment, aggravates the course of the disease and increases mortality. Сonclusions. Ensuring psychological well-being can be achieved by improving psychological care for cancer patients through influencing subjective, informational and organizational factors. An ideal strategy for patient management is joint work of psychologists and doctors, especially in communicating a diagnosis to patients, using and improving questionnaires, scales and criteria for assessing the need of cancer patients for psychological care. It is necessary to actively implement digital and mobile healthcare, Internet services, and telemedicine, for obtaining information and communication between patients and doctors and psychologists online, which will improve the positive aspects of psychological well-being.